Developing Learning Techniques While Learning Modern Teaching Methods Within the Framework of Teaching Methodology of Chemistry and Didactics of Science Subjects - SÓGOR, Csilla (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
In recent years, university instructors have observed that first-year students enrolled in the Faculty of Chemistry and Chemical Engineering possess a level of subject knowledge considerably below expectations, with many exhibiting fundamental deficiencies. Among students enrolled in the Hungarian-language programs of Chemistry and Chemical Engineering, 70% choose to complete the pedagogy module. Of these, 13.6% intend to work exclusively as chemistry teachers, while 18% remain undecided regarding their future career path. The rest plan to pursue research or engineering careers but do not exclude the possibility of teaching. At the beginning of their studies, 40% of respondents expressed the hope that the methodology courses would help them become more confident professionally and improve their own learning techniques. The first part of this study, the literature review, presents the thematic content covered in the methodology courses designed to develop students’ key competencies—skills they will later need to cultivate in their own pupils when teaching chemistry. The second part examines students’ learning habits, exploring how the pedagogy module contributes to their ability to develop autonomous and reflective learning strategies.